(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the multifaceted impact of classroom environment on student engagement and motivation, examining key factors such as physical space, social-emotional climate, and intellectual engagement. It delves into the profound influence of these factors on student learning and well-being, offering practical strategies for educators to cultivate a thriving learning space that fosters engagement, motivation, and academic success.